Pengaruh disiplin kerja, stress kerja dan kompensasi terhadap kinerja karyawan (Studi pada Karyawan PT Phapros, Tbk Kota Lama Semarang) - Triana Puji Rahayu; Lie . Liana (Al Tijarah, 2020)
This study aims to analyze the effect of work discipline, work stress, and compensation on employee performance. The population in this study were employees of PT. Phapros, Tbk Kota Lama Semarang, amounting to 84 employees. Data collection uses a survey method with a questionnaire as an instrument. The data is processed using the SPSS 22 program. Testing is done by validity test, reliability test, F test, determination coefficient test (R²), and hypothesis testing (t test). The results showed that work discipline had a positive and significant effect on employee performance, work stress had a positive and significant effect on employee performance, and compensation had no effect on employee performance.